One-Step Repair for Cartilage Defects in a Rabbit Model: A Technique Combining the Perforated Decalcified Cortical-Cancellous Bone Matrix Scaffold With Microfracture. (March 2014) - Dai, Linghui; He, Zhenming; Zhang, Xin; Hu, Xiaoqing; Yuan, Lan; Qiang, Ming; Zhu, Jingxian; Shao, Zhenxing; Zhou, Chunyan; Ao, Yingfang
Background: Cartilage repair still presents a challenge to clinicians and researchers alike. A more effective, simpler procedure that can produce hyaline-like cartilage is needed for articular cartilage repair. Hypothesis: A technique combining microfracture with a biomaterial scaffold of perforated decalcified cortical-cancellous bone matrix (DCCBM; composed of cortical and cancellous parts) would create a 1-step procedure for hyaline-like cartilage repair. Study Design: Controlled laboratory study. Methods: For the in vitro portion of this study, mesenchymal stem cells (MSCs) were isolated from bone marrow aspirates of New Zealand White rabbits. Scanning electron microscopy (SEM), confocal microscopy, and 1, 9-dimethylmethylene blue assay were used to assess the attachment, proliferation, and cartilage matrix production of MSCs grown on a DCCBM scaffold. For the in vivo experiment, full-thickness defects were produced in the articular cartilage of the trochlear groove of 45 New Zealand White rabbits, and the rabbits were then assigned to 1 of 3 treatment groups: perforated DCCBM combined with microfracture (DCCBM+M group), perforated DCCBM alone (DCCBM group), and microfracture alone (M group). Five rabbits in each group were sacrificed at 6, 12, or 24 weeks after the operation, and the repair tissues were analyzed by histological examination, assessment of matrix staining, SEM, and nanoindentation of biomechanical properties. Results: The DCCBM+M group showed hyaline-like articular cartilage repair, and the repair tissues appeared to have better matrix staining and revealed biomechanical properties close to those of the normal cartilage. Compared with the DCCBM+M group, there was unsatisfactory repair tissues with less matrix staining in the DCCBM group and no matrix staining in the M group, as well as poor integration with normal cartilage and poor biomechanical properties. Conclusion: The DCCBM scaffold is suitable for MSC growth and hyaline-like cartilage repair induction when combined with microfracture. Clinical Relevance: Microfracture combined with a DCCBM scaffold is a promising method that can be performed and adopted into clinical treatment for articular cartilage injuries.